2012
DOI: 10.2478/v10194-011-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

The history of Lake Rzecin and its surroundings drawn on maps as a background to palaeoecological reconstruction

Abstract: The article presents the results of landscape analysis of the surroundings of Lake Rzecin in Noteć Forest depicted on cartographic materials. Morphometrical analysis and analysis of changes in the water conditions of Lake Rzecin were conducted. Thanks to many cartographic data, changes in lake geometry could be observed during almost the whole of the last two centuries. The results show that the major impact on the rate of lake level decrease in the last two hundred years was due to melioration works. Two peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…A study by Barabach (2012) based on archival maps showed that moderate changes have occurred in the landscape of Rzecin area during the past 200 years. However, historical sources and palaeoecological data reveal a different pattern of change.…”
Section: Disturbance Trophic States and Hydrologymentioning
confidence: 99%
“…A study by Barabach (2012) based on archival maps showed that moderate changes have occurred in the landscape of Rzecin area during the past 200 years. However, historical sources and palaeoecological data reveal a different pattern of change.…”
Section: Disturbance Trophic States and Hydrologymentioning
confidence: 99%
“…The whole Rzecin peatland, which is considered a poor fen, covers an area of 114 hectares [39]. According to historical and cartographic data, the peatland is a result of lake shallowing, a decelerated but ongoing process [39,40]. At the middle of the peatland, there is a station where measurements of greenhouse gas exchange (CO 2 , CH 4 , H 2 O) have been carried out continuously since 2004 [41][42][43][44][45].…”
Section: Site Descriptionmentioning
confidence: 99%
“…According with old maps from the 18th and 19th centuries, in the southern part of the peatland was a natural spring. It was joined to a drainage ditch in the second half of the 19th century (Barabach, 2012). Kopytkowo is a nearly undisturbed fen located in the Middle Basin of the Biebrza Valley, near to the village Kopytkowo, Poland.…”
Section: Rzecin Wetland (Pl-wet)mentioning
confidence: 99%